Inhibitory effects of estradiol on inward rectifier and delayed rectifier K+ currents in guinea pig ventricular myocytes - Zhang Yi; Song Li-lin; Gu Shuang-zhen; Lu Shen-gui; Zhou Zhao-nian (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of estradiol (Est) on inward rectifier K+ (IK1) and delayed rectifier K+ (IK) channels in isolated guinea pig ventricular myocytes. METHODS: Using whole cell patch-clamp recording techniques. RESULTS: Est 10 mumol.L-1 and 100 mumol.L-1 decreased the action potential duration, APD50, from (474 +/- 71) ms to (330 +/- 75) ms and (229 +/- 67) ms (n = 7 cells of 7 guinea pigs, P < 0.05), respectively. Est 100 mumol.L-1 also decreased APD90 from (587 +/- 60) ms to (418 +/- 79) ms (n = 7, P < 0.05). Est inhibited IK tail current (IK.tail) concentration-dependently. IK.tail was depressed 53% (n = 5, P < 0.05) at 10 mumol.L-1 and 80% (n = 5, P < 0.01) at 100 mumol.L-1 compared with control. Est > or = 10 mumol.L-1 blocked IK1. The maximal inhibition of inward current of IK1 occurred at -100 mV test potential was 49% (n = 5, P < 0.01) and outward current of IK1 at -40 mV was 72% (n = 5, P < 0.01). The reverse potential shifted negatively, from -70 to -76 mV. CONCLUSION: Est possessed blocking effects on both IK1 and IK channels in guinea pig ventricular myocytes.